Phage Display of Adenovirus Type 5 Fiber Knob as a Tool for Specific Ligand Selection and Validation - Pereboev, Alexander (American Society for Microbiology, 2001)
Adenovirus (Ad) vectors are most potent for use as gene delivery vehicles to infect human cells in vitro and in vivo with high efficiency. The main limitation in utilization of Ad as a gene transfer vector is the lack of specificity. Genetic modifications of Ad capsid proteins resulting in incorporation of foreign polypeptide ligand sequences can redirect the vector towards target cells. However, in many cases the incorporated ligands lose specificity or lead to conformational changes influencing virion integrity. In order to select target-specific ligands a priori structurally compatible with Ad, we propose a system for displaying polypeptide sequences in the context of the Ad fiber knob on the surfaces of filamentous bacteriophages. To establish this concept, we displayed the wild-type Ad serotype 5 knob and knobs containing c-Myc epitopes and six-histidine sequences in the pJuFo phage system. The knobs remained trimeric and bound the coxsackievirus-Ad receptor, and the phage knob-displayed ligands recognized and bound their cognates in the phage-displayed knob context. Further development of this system may be useful for candidate ligand fidelity and Ad structural compatibility validation prior to Ad modification.